Determination of the endpoints of partial deletion mutants of the attachment site of bacteriophage lambda by DNA sequencing. - Davies, R W (1978)
The deletion mutants b508 and b522 of bacteriophage lambda both end within the attachment site. The formation of such deletions is dependent upon the presence of intact integrase, and thus the deletion endpoints may be related to the normal crossover site in site-specific recombination. We have determined the DNA sequences of the attachment site regions of these deletions. Comparison of the sequences with lambda wildtype shows that both the deletions end within the central common homology region but at different positions. The consequences of these findings for current models of site-specific recombination are discussed.